Adaptive Response of Thermophiles to Redox Stress and Their Role in the Process of dye Degradation From Textile Industry Wastewater - Aragaw, Tadele Assefa; Bogale, Fekadu Mazengiaw; Gessesse, Amare (Frontiers in Physiology, 2022)
Release of dye-containing textile wastewater into the environment causes severe pollution with serious consequences on aquatic life. Bioremediation of dyes using thermophilic microorganisms has recently attracted attention over conventional treatment techniques. Thermophiles have the natural ability to survive under extreme environmental conditions, including high dye concentration, because they possess stress response adaptation and regulation mechanisms. Therefore, dye detoxification by thermophiles could offer enormous opportunities for bioremediation at elevated temperatures. In addition, the processes of degradation generate reactive oxygen species (ROS) and subject cells to oxidative stress. However, thermophiles exhibit better adaptation to resist the effects of oxidative stress. Some of the major adaptation mechanisms of thermophiles include macromolecule repair system; enzymes such as superoxide dismutase, catalase, and glutathione peroxidase; and non-enzymatic antioxidants like extracellular polymeric substance (EPSs), polyhydroxyalkanoates (PHAs), etc. In addition, different bacteria also possess enzymes that are directly involved in dye degradation such as azoreductase, laccase, and peroxidase. Therefore, through these processes, dyes are first degraded into smaller intermediate products finally releasing products that are non-toxic or of low toxicity. In this review, we discuss the sources of oxidative stress in thermophiles, the adaptive response of thermophiles to redox stress and their roles in dye removal, and the regulation and crosstalk between responses to oxidative stress.